Бешеные бабки в 6 "Б": повесть : [для среднего школьного возраста] / Людмила Матвеева - Матвеева Людмила Григорьевна (АСТ, 2010)
Экземпляры: ДБаб (20170727) / Инвентарный номер: 49596 / Цена: 152.00 / Авт.знак: М 333 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6